WORKSHOP SENI KALIGRAFI DENGAN TEKNIK CETAK TINGGI DENGAN PUBLIKASI VIA YOUTUBE - Sigit Purnomo Adi; Pande Made Sukerta; Martinus Dwi Marianto; Sri Hadi (LP2MP3M, INSTITUT SENI INDONESIA SURAKARTA, 2022)
Abstract The purpose of this community service is to provide application and understanding of the importance of making publications via YouTube, as a means of introducing that documentation is not only for individuals or institutions, but can be disseminated throughout the world through online media. The problem regarding the publication of works is indeed very vital, for that apart from the workshop technically the creation, it is also supported by publication via YouTube. This high-print technique calligraphy art workshop also uses YouTube publications, so that the workshop process and its work or results can be widely enjoyed and appreciated. This workshop or community service uses 3 stages, namely location identification, training and also work evaluation. The impact of this community service is that this workshop is able to educate and also inspire people who see it, because it is disseminated through online media, namely uploading workshop documentation videos via the Makmoer channel Art project.